Clinical Outcome of Isolated Serous Tubal Intraepithelial Carcinomas (STIC). Issue 9 (1st November 2013) - Wethington, Stephanie L.; Park, Kay J.; Soslow, Robert A.; Kauff, Noah D.; Brown, Carol L.; Dao, Fanny; Otegbeye, Ebunoluwa; Sonoda, Yukio; Abu-Rustum, Nadeem R.; Barakat, Richard R.; Levine, Douglas A.; Gardner, Ginger J.
Abstract : Objective: Risk-reducing salpingo-oophorectomy (RRSO) is recommended for women with BRCA mutation due to increased risk of pelvic serous carcinoma. Serous tubal intraepithelial carcinoma (STIC) is a pathologic finding of unknown clinical significance. This study evaluates the clinical outcome of patients with isolated STIC. Materials/Methods: We retrospectively reviewed the medical records of consecutive patients with a germline BRCA1/2 mutation or a high-risk personal or family history of ovarian cancer who underwent RRSO between January 2006 and June 2011. All patients had peritoneal washings collected. All surgical specimens were assessed using the sectioning and extensively examining the fimbria protocol, with immunohistochemistry when indicated. p53 signature lesions and secretory cell outgrowths were excluded. Results: Of 593 patients who underwent RRSO, isolated STIC was diagnosed in 12 patients (2%). Five patients (42%) were BRCA1 positive, 5 patients (42%) were BRCA2 positive, and 2 patients (17%) had high-risk family history. Preoperatively, all patients with STIC had normal CA-125 levels and/or pelvic imaging results. Seven patients underwent hysterectomy and omentectomy, 6 patients (46%) had pelvic node dissections, and 5 patients (39%) had para-aortic node dissections. With the exception of positive peritoneal washings in 1 patient, no invasive or metastatic disease was identified. No patient received adjuvant chemotherapy. At median follow-up of 28 months (range, 16–44 months), no recurrences have been identified. Conclusions: Among the cases of isolated STIC after RRSO reported in the literature, the yield of surgical staging is low, and short-term clinical outcomes are favorable. Peritoneal washings are the most common site of disease spread. Individualized management is warranted until additional data become available.